Kerjasama Orang Tua Dan Guru Dalam Pembinaan Praktik Ibadah Harian Anak Berkebutuhan Khusus Di Sekolah Luar Biasa Negeri Pidie Jaya - Nurul A'liyah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Cooperation is an effort carried out together to achieve a goal, involving two or more parties. Cooperation in fostering the daily worship of students will also involve two parties, namely parents and teachers. The problem arising in this study lies in the cooperation of parents and teachers in fostering the daily worship practices of children with special needs at SLB Negeri (public special school) in Pidie Jaya, emerging inquiries such as the types of effort made by both parents and teachers, the form of cooperation that exists between the two parties, and the obstacles encountered in fostering the worship practices. The method used in this study was a qualitative research method with a descriptive analysis. Data collection techniques were observation, interview, and documentation. The results showed that both parents and teachers have made some efforts to help children with special needs practice prayers. The types of cooperation that the parents and teachers have performed included establishing communication by calling or writing notices in student books, organizing meetings, making correspondence to invite parents to school, and visiting students’ homes when necessary. The inhibiting factors for the cooperation between the parents and teachers were some parents’ unwillingness to attend the meetings and their lack of commitment to actively participate in working with the teachers in fostering their special-needs children.